Peranan Guru Agama Hindu Dalam Penumbuhkembangan Karakter Siswa Di SMA Dwijendra Denpasar - Putu Angga Sascita Hardiana; Ni Komang Sutriyanti; I Putu Andre Suhardiana (Kamaya: Jurnal Ilmu Agama, 2019)
Education is a universal activity of human life since it exists almost in all parts of the world. Education is essentially a human effort to humanize human beings themselves. Education is a process of human interaction between educator and students to achieve educational goals. Based on the background described above, the main problems in this study could be formulated as follows: (1) How is the form of the development of students’ character by the Hindu religion teacher at Dwijendra High School Denpasar? (2) What are the obstacles told by the Hindu religion teacher in the development of students’ character in Dwijendra High School Denpasar? (3) What are the efforts made by the Hindu religion teacher to overcome obstacles in developing the students’ character in Dwijendra High School Denpasar? This research was classified as qualitative research. The theories used were Structural-Functional Theory, Convergence Theory, and Stimulus-Response Theory. Data were obtained through observation, interview, documentation, and literature study methods. The collected data were then analyzed by a qualitative descriptive method with steps of data reduction, data presentation, and conclusion drawing.The results of the study showed that the form of the development of the students’ character by the Hindu religion teacher in Dwijendra High School Denpasar was (1). Character development was conducted through several activities, such as Intra Curricular Activities, Co-Curricular Activities, and Extra Curricular Activities. Those three activities had a major contribution to developing the character of students in school. Moreover, the teacher is an important figure in the course of character development in all three curricular activities. The obstacles faced by the Hindu religion teacher in developing students' character in Dwijendra High School Denpasar were (1) internal obstacles, namely students' interests, emotional and students' talents. (2) external obstacles namely the outside factors of students such as the influence of broken families, school, community environment, and the influence of mass media. Efforts made by Hindu religion teacher to overcome the obstacles to develop the students’ character in Dwijendra High School Denpasar were done by: (1). Enforcing discipline. (2). Monitoring continuously. (3). Developing an atmosphere of the learning environment.